2019
DOI: 10.1177/0733464819879015
|View full text |Cite
|
Sign up to set email alerts
|

Moving to a Continuing Care Retirement Community or Staying in the Community? A Comparison Between American and Israeli Older Adults

Abstract: Using the theory of diffusion of innovations, this study examined differences between American and Israeli older adults who decided to move to continuing care retirement communities (CCRC) and American and Israeli older adults who decided to stay at home. A total of 101 American participants (52 residents, 49 nonresidents) and 154 Israeli participants (104 residents, 50 nonresidents) completed measures of attitudes toward CCRCs, well-being, limitations in daily living, health status, proximity to services, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The data used in this longitudinal observational cohort study was collected from a Beijing continuing care retirement community (CCRC) (15)(16)(17), which could provide friendly living environment, convenient medical services, and strong social support for the residents. The independent residents were assessed by community physicians before living in the CCRC active area.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The data used in this longitudinal observational cohort study was collected from a Beijing continuing care retirement community (CCRC) (15)(16)(17), which could provide friendly living environment, convenient medical services, and strong social support for the residents. The independent residents were assessed by community physicians before living in the CCRC active area.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The consideration of future needs is one of the most important factors contributing to older adults’ relocation to CCRCs, such as seeking continuing care, releasing the burden of household upkeep and maintenance and reducing the burden to family members (Krout et al , 2002). Nevertheless, it should be noted that the factors influencing different older adults’ relocation to CCRCs are varied given their different cultural background (Shinan-Altman et al , 2020). Historical studies have reported various benefits of living in CCRCs.…”
Section: Background Literaturementioning
confidence: 99%
“…Compared with other residential settings, the CCRCs provide at least some autonomy for older residents, at least upon their rst entering as independent residents [9]. When people age, become progressively incapacitated and lose their independence, they can move to more intensive levels of care in the same setting [10]. However, CCRCs are still in their infancy in China, in contrast to those in western countries, which are rmly established, widely marketed and well-regulated housing options for older adults [8].…”
Section: Introductionmentioning
confidence: 99%